Liberdade e Coexistência: A Sociedade Pós-Emancipação nas Planícies Colombianas do Pacífico - Vital, André Vasques (Fronteira: Journal of Social, Technological and Environmental Science, 2019)
Book Review: Leal C 2018. Landscapes of freedom: building a postemancipation society in the rainforests of western Colombia. The University of Arizona Press, Tucson, 352 pp.